Cross-cultural adaptation and validation of the childbirth fear prior to pregnancy scale in Brazil - Tomazin, Kelly Jaqueline da Costa Galinari [UNESP]; Miot, Hélio Amante [UNESP]; Stoll, Kathrin; Gonçalves, Ivana Regina [UNESP]; Spiri, Wilza Carla [UNESP]; Felipe, Tânia Roberta Limeira [UNESP]; Jamas, Milena Temer [UNESP] (Bentham Science Publishers, 2021)
Background: The fear of childbirth can range from apprehension to intense fear (tokophobia), with serious consequences for maternal health. Therefore, a standardized scale is needed to measure the fear of childbirth before pregnancy. Objective: This study aimed to adapt the Childbirth Fear Prior to Pregnancy (CFPP) scale to the Brazilian context and analyse its validity and reliability. Methods: A cross-sectional survey was completed by 146 nursing students at two Brazilian universities. A committee of experts evaluated the cross-cultural adaptation of the CFPP scale. Construct validity was verified using item-total correlations and Exploratory Factor Analysis (EFA). The validity of divergent concurrent criteria was evaluated by associating the score obtained using the Brazilian CFPP with the Depression, Anxiety, and Stress Scale (DASS-21). Reliability was analysed using Cronbach’s alpha coefficient and test-retest. Results: Correlation analysis revealed a predominance of moderate inter-item correlation and strong item-total correlation (>0.62). The EFA indicated that all items related to a single factor, with factor loadings and communalities >0.5. These results reinforced the one-dimensionality of the Brazilian CFPP. The validity of divergent concurrent criteria was confirmed via weak correlations with DASS-21 scores (r = 0.32, p < 0.001). The Cronbach’s alpha (0.86) and the intra-class correlation coefficient (0.99) indicated reliability and strong temporal stability, respectively. Conclusion: The Brazilian version of the CFPP provides evidence of validity and reliability to measure fear of childbirth before pregnancy in young adults in Brazil.
Keywords: Childbirth fear; Psychometrics; Scale; Surveys and questionnaires; Transcultural studies; Validation studies